P26 enhances baculovirus gene delivery by modulating the mammalian antiviral response - Plastine, María del Pilar; López, María Gabriela; Gravisaco, María José; Taboga, Oscar; Alonso, Victoria (Springer Nature, 2023)
Poxins are poxviral proteins that act by degrading 2´3´-cGAMP, a key molecule of cGAS-STING axis that drives and amplifies the antiviral response. Previous works have described some poxin homologous among lepidopteran and baculoviral genes. In particular, P26, a poxin homologous from AcMNPV retains the 2´3´-cGAMP degradation activity in vitro. In this work, we demonstrated that the antiviral activity triggered by baculovirus was disrupted by the transient expression of P26 in murine and human cell lines, and the effect of this action is not only on IFN-β production but also on the induction of IFN-λ. Besides, we proved P26 functionality in a stable-transformed cell line where the protein was constitutively expressed, preventing the production of IFN-β induced by baculovirus and resulting in an improvement in the transduction efficiency by the attenuation of the antiviral activity. Finally, we incorporated P26 into budded virions by capsid display or passive incorporation, and the results showed that both strategies resulted in an improvement of 3–17 times in the efficiency of transgene expression in murine fibroblasts. Our results suggest that the incorporation of P26 to budded baculoviral vectors is a very promising tool to modulate negatively the innate antiviral cellular response and to improve the efficiency of gene delivery in mammalian cells.
Keywords: Ciencias médicas y de la salud::Biotecnología médica